Modernism meets its Mac. - Phillips, Jon (Mac life)
You already use your computer to make your own music, edit your own photos, and create your own movies--so why pay someone else to decorate your home? Your Mac is the perfect tool for giving your interior space a dash of 21st-century modernism. Follow along and we'll show you how.